Human Resource Management Activities and Organizational Commitment among the Engineers and Technical Technicians of the Electricity Company - Sajjad Salehi-Kordabadi; Mehrdada Godarzvand Chegini; Shahram Ismaeilpoor; Farzane Zad-Dousti (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: One of the strategic issues of Guilan Regional Electricity Company is planning and providing appropriate communication methods to attract the employees' participation to improve continuously, increase the efficiency and effectiveness of activities, create added value, active and lively environment, maintain intellectual capital, and create change. By institutionalizing learning, the study aims to develop organizational innovation and growth. Methodology: The research method is correlation, and the field data collection method and data collection tool are questionnaires. In the present study, 79 complete questionnaires were obtained using the random sampling method, and the research hypotheses were tested using the Pearson correlation test. Findings: The results indicate a positive relationship between human resource functions (service compensation, employee training and development, and top management support) and employees' organizational commitment. Originality/Value: The present study highlights the relationship between human resource functions (service compensation, employee training and development, and support for the organization's top management) and the organizational commitment of the company's engineers and technicians.